2016
DOI: 10.1111/bjd.14720
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance and impact of the CXCR4-CXCR7-CXCL12 axis in primary cutaneous melanoma

Abstract: CXCR4 expression defines a potential prognostic biomarker for AJCC stage II melanoma. Moreover, targeting the CXCR4-CXCR7-CXCL12 axis may represent a novel therapeutic strategy to prevent early melanoma progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
1
24
1
Order By: Relevance
“…Consistent with our ndings, McConnell et al demonstrated that patients with AJCC stage II melanomas had 3-fold risk of disease reoccurrence in individuals with high total CXCR4 expression (>50%). Nevertheless, CXCL12 over-expression in the adjacent epidermis of all melanoma stages with tumour progression was associated with increased time to metastasis [35]. Due to the autocrine and paracrine CXCL12 secretion, the contradictory phenomenon remains to be further studied.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with our ndings, McConnell et al demonstrated that patients with AJCC stage II melanomas had 3-fold risk of disease reoccurrence in individuals with high total CXCR4 expression (>50%). Nevertheless, CXCL12 over-expression in the adjacent epidermis of all melanoma stages with tumour progression was associated with increased time to metastasis [35]. Due to the autocrine and paracrine CXCL12 secretion, the contradictory phenomenon remains to be further studied.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, different crosstalk between MAFs and melanoma cells are involved in metastasis of melanoma cells. For example, CXCR4 (CXC chemokine receptor-4) is expressed on the surface of melanoma cells, while its ligand CXCL12 is released by MAFs in the tumor microenvironment, promoting the migration and metastasis of melanoma cells to distal metastatic sites through interaction with CXCR4 expressed on tumor cells ( 277 – 279 ). Besides, HGF secreted by MAFs induce fibronectin expression and associated matrix assembly, which promotes melanoma cell metastasis ( 280 ).…”
Section: Melanomamentioning
confidence: 99%
“…Potential intracellular biomarkers associated with melanoma transformation. in stage II melanoma (66). Another potential intracellular biomarker is cytotoxic T-lymphocyte associated protein 4 (CTLA4), which is upregulated during the transformation to melanoma, and in the list of the top 50 modulated genes (Fig.…”
Section: Differential Expression Levelsmentioning
confidence: 99%